Energy efficiency and productivity improvements analysis in a Brazilian steel plant: simulation model using JaamSim open source software - Rodrigo de Paula Oliveira; Wilson Trigueiro de Sousa Júnior; Roberta Alves; Alexandre Ferreira de Pinho; Helio Tavares de Sá Neto (Discover Energy)
Abstract The Brazilian steel sector, inserted in a scenario of crisis and competitiveness, is going through a moment when optimization procedures in the production process are well regarded. However, issues related to sustainability, such as controls on energy consumption and carbon dioxide ( $$\hbox {CO}_{2}$$ CO 2 ) emissions, are also fundamental to be considered as analysis variables since the demand for actions that preserve the ecosystem and aim at the conscientious consumption of resources has increased. An important technical tool that can help to address these factors together is Discrete Event Simulation (DES), a well-known computational simulation method to support decision-making. Still hardly used to explore issues related to sustainability, a DES model allows the representation of an existing system in a virtual space, providing an ideal environment for conducting experiments, without the need to make changes in practice. Thus, this paper applied the DES method in a steelmaker located in Brazil, in order to simulate the impact, after a possible change in the system, on the behavior of three analysis variables: production volume, electrical energy consumption, and $$\hbox {CO}_{2}$$ CO 2 emission. The use of a discrete event simulation methodology and JaamSim®open-source software, provided a low-cost solution and allowed the simulation of results in the virtual scenario, after modification. As a result, in the alternative scenario, daily production increased by almost 87% and the total electrical energy consumption decreased by 38.2%, a total saving of 100,440.6 kilowatts per hour, which is equivalent to 71.2 metric tons of avoided $$\hbox {CO}_{2}$$ CO 2 emission.